Pengaruh Return on Asset, Net Profit Margin dan Current Ratio Terhadap Harga Saham Food and Beverage di Bursa Efek Indonesia - Januardin Manullang; Nanda Pratiwi; Refiensa Yohana Sihombing; Rifka Aulia Harahap; Kevin Christian Tampubolon (Politeknik Ganesha Medan, 2021)
This study aims to examine the effect of Return on Asset, Net Profit Margin and Current Ratio on Food and Beverage Stock Prices listed on the Indonesia Stock Exchange for the 2014-2018 period. The population in this study were all companies in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange, amounting to 15 companies with a sample of 11 companies with the 2014-2018 period for 5 years and using a sampling technique, namely purposive sampling. The method of analysis used in this research is the Multiple Linear Regression Method. This research uses quantitative research. This type of research is descriptive statistics and the nature of the research is explanatory. The results of this study indicate that partially (t) Return On Asset and Net Profit Margin have no and insignificant effect on Stock Prices, while Current Ratio has a negative effect on Food and Beverage Stock Prices which simultaneously affect Return On Asset, Net Profit Margin, and Current Ratio. to the Food and Beverage Stock Price